2020
DOI: 10.1242/jeb.219501
|View full text |Cite
|
Sign up to set email alerts
|

Habituation of the cardiovascular responses to restraint stress is inhibited by exposure to other stressor stimuli and exercise training

Abstract: This study evaluated the effect of exposure to either a chronic variable stress (CVS) protocol or social isolation, as well as treadmill exercise training, in the habituation of the cardiovascular response upon repeated exposure to restraint stress in rats. The habituation of the corticosterone response to repeated restraint stress was also evaluated. For this, animals were subjected to either acute or 10 daily sessions of 60 min of restraint stress. CVS and social isolation protocols lasted for 10 consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 62 publications
(121 reference statements)
1
6
0
Order By: Relevance
“…This pattern of habituation is such different from those identified for the cardiovascular responses. Similar to that recently documented [1,2], our study showed that habituation of the cardiovascular responses to restraint could be observed mainly in terms of a faster return of HR and MAP to baseline values during the recovery period from the restraint stress. However, the values during the tenth session were similar to those observed during the acute restraint session.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This pattern of habituation is such different from those identified for the cardiovascular responses. Similar to that recently documented [1,2], our study showed that habituation of the cardiovascular responses to restraint could be observed mainly in terms of a faster return of HR and MAP to baseline values during the recovery period from the restraint stress. However, the values during the tenth session were similar to those observed during the acute restraint session.…”
Section: Discussionsupporting
confidence: 89%
“…However, the values during the tenth session were similar to those observed during the acute restraint session. Taken together, the corticosterone and cardiovascular responses to stress indicate that habituation may be system specific rather than a generalized body response [2].…”
Section: Discussionmentioning
confidence: 98%
“…This habituation process is proposed as a adaptative mechanism that limit the consequences of chronic stress (Bennett et al., 2018; Grissom & Bhatnagar, 2009; Herman, 2013; McCarty, 2016). However, recent evidence indicated that habituation of the cardiovascular changes to restraint stress is less pronounced in relation to, for instance, the HPA axis response (Benini et al., 2020; Santos et al., 2020). Accordingly, several cardiovascular changes have been reported following repeated exposure to restraint stress, including increase in arterial pressure (Bruder‐Nascimento et al., 2012, 2015; Duarte et al., 2015b; Duarte, Planeta, et al., 2015; Habib et al., 2015; Yang et al., 2014), without changes in HR (Daubert et al., 2012; Duarte et al., 2015b; Duarte, Planeta, et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The animals were maintained for a period of 60 min into the restraint tube 5 , 13 , 27 . Each animal was submitted to only one session of stress in order to avoid habituation 61 63 .…”
Section: Methodsmentioning
confidence: 99%